Challenges in implementing problem-based learning (PBL) - Engku Ibrahim, Engku Haliza (Universiti Brunei Darussalam. Sultan Hassanal Bolkiah Institute of Education, 2007)
The purpose of this paper is to describe an experience of integrating problem-based learning (PBL) in an introductory Sociolinguistics course for undergraduates. It is undoubted that the benefits of problem-based learning are numerous. However, in order to successfully implement problem-based learning, there are many challenges that would have to be overcome. This paper discusses some of the difficulties that PBL practitioners would have to face. Among others, one of the biggest challenges is the change in the role of the teacher in the PBL classroom. This paper focuses on the various challenges that a PBL practitioner faces and suggests ways in which these challenges could be tackled. The major concern of this paper is to advocate the integration of PBL strategies in classroom instruction as a way of promoting active learning.